PENGARUH GENDER, INTELLIGENT QUOTIENT (IQ), EMOTIONAL QUOTIENT (EQ) DAN SPIRITUAL QUOTIENT (SQ) TERHADAP PERTIMBANGAN PEMBERIAN OPINI AUDITOR - Suprihatin, Maylani; Wahyuni, Endang Dwi; Kurniawati, Eris Tri (Jurnal Reviu Akuntansi dan Keuangan)
The purpose of this study is to examine the effect of gender, intelligent quotient, emotionalquotient and spiritual quotient on the judgment of the auditor’s opinion. Therefore, researcheruses a quantitative methods with SPSS as an analytical tool in this study. The results showthat men and women do not have a significant difference based on psychological aspects that saywomen have a tendency to be more efficient and more thorough in decision making. On the otherhand, The higher of intellectual and emotional intelligence then giving the auditor’s opinion willalso increase well. Another finding is the higher of spiritual intelligence the more he can survivein the face of difficulties during performing his duties so that it will affect the conclusions of theexamination set forth in the opinion of auditorsKe y wo rds: Auditors Opinion, Emotional Quotient, Gender, Intellegent Quotient, SpiritualQuotient.